PCR-Based Identification and Characterization of Fusarium sp. Associated with Mango Malformation. (14th December 2010) - Arif, M.; Pani, D. R.; Zaidi, N. W.; Singh, U. S.
Abstract : Mango malformation is the most serious disease of mango causing considerable damage to the mango orchards worldwide. It is a major threat for mango cultivation in north Indian belt. In recent years, Fusarium sp. is finding wide acceptability in scientific community as a causal agent of this disease. However, little information is known about the variability in Fusarium isolates from malformed mango tissues. Therefore, the major objective of present study was the identification and analysis of genetic diversity among Fusarium isolates collected from malformed mango tissues. Two texon selective primers, ITS-Fu-f and ITS-Fu-r, were used for quick identification of Fusarium spp. The fungal genomic DNA was extracted from using CTAB method and was utilized as template for PCR amplification. Total 224 bands were amplified by 18 RAPD primers at an average of 12.44 bands per primer. The size of the obtained amplicons ranged from 0.264 kb (minimum) to 3.624 kb (maximum). Data scored from 25 isolates of Fusarium sp. with 18 RAPD primers were used to generate similarity coefficients. The similarity coefficient ranged from 0.17 to 0.945. Based on DNA fingerprints, all isolates were categorized into two major clusters. This study indicated a wide variability among different isolates of Fusarium .